Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1097/00005792-200009000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hut Lung: A Domestically Acquired Particulate Lung Disease

Abstract: We report an illustrative case of advanced "hut lung," or domestically acquired particulate lung disease (DAPLD), in a recently emigrated nonsmoking Bangladeshi woman with a history of 171 hour-years of exposure to biomass smoke. She presented with symptoms of chronic cough, dyspnea, and early parenchymal lung disease. High-resolution computed tomography (CT) of the chest demonstrated numerous 2- to 3-mm nodules, sparing the pleural surface. To our knowledge, this is the first such report of CT findings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 30 publications
4
48
0
10
Order By: Relevance
“…[1][2][3][4][5][6] The terms "hut lung" or "domestically acquired particulate lung disease" have been used to describe the condition. 7 A diagnostic feature in anthracosis is the black-colored deposits along the airway or lymph nodes. Problems caused by chronic exposure to biomass smoke and other particulates, such as dust or silicates from food grinding, are becoming more relevant in the western world due to immigration.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The terms "hut lung" or "domestically acquired particulate lung disease" have been used to describe the condition. 7 A diagnostic feature in anthracosis is the black-colored deposits along the airway or lymph nodes. Problems caused by chronic exposure to biomass smoke and other particulates, such as dust or silicates from food grinding, are becoming more relevant in the western world due to immigration.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution, biomass smoke and cigarette smoke are also known as the other enviromental factors for anthracosis [1][2][3][4][5]. The term "anthracotic" is usually used to describe coal and other black pigments of which carbon is a major constituent.…”
Section: Introductionmentioning
confidence: 99%
“…Anthracosis is a form of pneumoconiosis which is not only caused by coal dust, but also by other environmental factors such as air pollution, biomass fuels used extensively for cooking ("hut lung"), and cigarette smoking (13)(14)(15)(16)(17)(18). It has been recently demonstrated that the presence of microscopic anthracotic pigment in EBUS-TBNA of enlarged lymph nodes is negatively associated with lymph node malignancy (19).…”
Section: Discussionmentioning
confidence: 99%